Composition for electrochemical element functional layer, electrochemical element functional layer, and electrochemical element
By using a composition with a granular polymer, a bonding material and an inorganic particle with specified characteristics, a single functional layer is formed, and the existing spacer manufacturing process is complicated and the heat resistance and adhesion are difficult to take into account, thereby achieving an efficient and simplified manufacturing process and excellent electrochemical characteristics.
Patent Information
- Application Number
- CN202080005815.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-02-28
- Filing Date
- 2020-02-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-02-19
AI Technical Summary
In the manufacture of the existing lithium-ion secondary battery spacer, the heat-resistant layer and the adhesive layer need to be implemented sequentially. The steps are complicated, and there is a trade-off relationship between heat resistance and adhesiveness, making it difficult to achieve excellent heat resistance and adhesiveness at the same time.
A composition containing a particulate polymer having a predetermined average roundness and a volume average particle size, a bonding material, and an inorganic particle are formed to form a single functional layer capable of simultaneously exhibiting heat resistance and adhesion.
The powder loss phenomenon in the functional layer is effectively suppressed, while ensuring sufficient heat resistance, the adhesiveness is significantly improved, the manufacturing process of the spacer is simplified, and the productivity is improved.
Smart Images

Figure BDA0003035662140000421 
Figure BDA0003035662140000431 
Figure BDA0003035662140000441
Abstract
Description
Technical Field
[0001] The present invention relates to a composition for an electrochemical device functional layer, a functional layer for an electrochemical device, and an electrochemical device. Background Art
[0002] Electrochemical devices such as lithium-ion secondary batteries and electric double layer capacitors are used in a wide range of applications because they are small and lightweight, have high energy density, and can be repeatedly charged and discharged.
[0003] Here, for example, a lithium ion secondary battery generally includes a positive electrode, a negative electrode, and battery components such as a separator that separates the positive electrode from the negative electrode to prevent a short circuit between the positive electrode and the negative electrode.
[0004] Furthermore, in recent years, further improvements in separators have been studied in order to further improve the performance of lithium secondary batteries.
[0005] Specifically, for example, Patent Document 1 proposes a separator in which a heat-resistant layer containing non-conductive particles and a binder is formed on a separator substrate, and an adhesive layer containing a predetermined particle polymer is further provided on the heat-resistant layer. In addition, Patent Document 1 also reports that by using a separator having an adhesive layer on the heat-resistant layer, the separator and the electrode can be well bonded, thereby improving the battery characteristics of the secondary battery.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: International Publication No. 2013 / 151144. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] However, the above conventional separator having a heat-resistant layer and an adhesive layer needs to be produced by sequentially forming the heat-resistant layer on the separator substrate and the adhesive layer on the heat-resistant layer, which complicates the production process.
[0011] Therefore, in order to solve such a problem, it is considered to simplify the manufacturing process of the spacer and improve productivity by forming a single layer that can simultaneously exhibit heat resistance and adhesion (hereinafter such a layer is referred to as a "functional layer") on the spacer substrate instead of separately providing a heat-resistant layer and an adhesive layer.
[0012] Therefore, the inventors are concerned that if a composition containing a component that contributes to heat resistance and a component that contributes to adhesion is used, heat resistance and adhesion can be simultaneously exhibited in the obtained functional layer. However, after research, the inventors have made it clear that in a functional layer formed by mixing only a component that contributes to heat resistance and a component that contributes to adhesion to form a composition and using the composition, the components constituting the functional layer will fall off (hereinafter referred to as "powdering"). In addition, it is also clear that since there is a trade-off relationship between heat resistance and adhesion, it is not easy to form a functional layer that can exert excellent adhesion while ensuring sufficient heat resistance.
[0013] Therefore, an object of the present invention is to provide a technology capable of effectively forming a functional layer for an electrochemical element that can suppress powder loss and exhibit excellent adhesiveness while ensuring sufficient heat resistance.
[0014] Solutions for solving problems
[0015] The present inventors have conducted intensive research to achieve the above-mentioned purpose. The present inventors have found that, by using a composition containing a granular polymer having a predetermined average roundness and a predetermined volume average particle size, a binder, and inorganic particles, a functional layer that can suppress powder loss and exhibit excellent adhesion while ensuring sufficient heat resistance can be effectively formed, thereby completing the present invention.
[0016] That is, the present invention aims to solve the above-mentioned problems advantageously, and the composition for the electrochemical element functional layer of the present invention is characterized in that it comprises a granular polymer, a binder and inorganic particles, the average circularity of the granular polymer is greater than 0.90 and less than 0.99, and the volume average particle size of the granular polymer is greater than 1.0 μm and less than 10.0 μm. In this way, if a granular polymer having a predetermined average circularity and a predetermined volume average particle size is used in combination with a binder and inorganic particles, a functional layer for an electrochemical element that can suppress powdering and can exhibit excellent adhesion while ensuring sufficient heat resistance can be effectively formed.
[0017] In the present invention, the "average circularity" and the "volume average particle size" can be measured by the method described in the Examples of the present specification.
[0018] Here, the composition for the electrochemical element functional layer of the present invention preferably has a particle size distribution of the above-mentioned granular polymer of 1.10 or more and 1.50 or less. If the particle size distribution of the granular polymer is within the above range, the electrochemical element functional layer formed using the electrochemical element functional layer composition can change with the change of the electrochemical element. In addition, it is also possible to suppress the deviation of the electrochemical element functional layer after the components are bonded to each other through the electrochemical element functional layer, and improve the electrochemical characteristics of the electrochemical element.
[0019] In the present invention, the "particle size distribution" can be measured using the method described in Examples of the present specification.
[0020] In addition, in the composition for electrochemical element functional layer of the present invention, the mixing ratio of the inorganic particles and the granular polymer is preferably 95:5 to 55:45 by volume. If the mixing ratio of the inorganic particles and the granular polymer is within the above range by volume, the balance between heat resistance and adhesion is good in the electrochemical element functional layer formed using the composition for electrochemical element functional layer.
[0021] Furthermore, in the composition for an electrochemical element functional layer of the present invention, the glass transition temperature of the above-mentioned particulate polymer is preferably 10° C. to 90° C. If the glass transition temperature of the particulate polymer is within the above range, in the electrochemical element functional layer formed using the composition for an electrochemical element functional layer, it is possible to suppress the adhesion of the electrochemical element functional layer while ensuring good adhesion.
[0022] In the present invention, the "glass transition temperature" can be measured using the method described in Examples of the present specification.
[0023] Moreover, in the composition for the electrochemical element functional layer of the present invention, it is preferred that the above-mentioned granular polymer contains an aromatic vinyl monomer unit. By making the granular polymer contain an aromatic vinyl monomer unit, the adhesion of the electrochemical element functional layer formed using the electrochemical element functional layer composition to the substrate can be improved. In addition, the dissolution amount of the granular polymer in the electrolyte can be reduced, thereby enabling the output characteristics of the electrochemical element to be excellent.
[0024] In the present invention, a polymer “including a monomer unit” means that “a polymer obtained using the monomer includes a structural unit derived from the monomer”.
[0025] In addition, the present invention aims to solve the above-mentioned problems advantageously, and the electrochemical element functional layer of the present invention is characterized in that it is formed using any of the above-mentioned electrochemical element functional layer compositions. Thus, if the electrochemical element functional layer composition of the present invention is used, it is possible to provide an electrochemical element functional layer that can suppress powder loss and can exhibit excellent adhesion while ensuring sufficient heat resistance.
[0026] The present invention aims to solve the above-mentioned problems, and the electrochemical device of the present invention is characterized by having the above-mentioned electrochemical device functional layer. Thus, by having the electrochemical device functional layer of the present invention, an electrochemical device that can exhibit excellent electrochemical characteristics can be provided.
[0027] Effects of the Invention
[0028] According to the present invention, it is possible to provide a composition for an electrochemical element functional layer that can effectively form an electrochemical element functional layer that can suppress powder loss and can exhibit excellent adhesiveness while ensuring sufficient heat resistance.
[0029] Furthermore, according to the present invention, it is possible to provide a functional layer for an electrochemical element that can suppress powdering and exhibit excellent adhesiveness while ensuring sufficient heat resistance.
[0030] Furthermore, according to the present invention, it is possible to provide an electrochemical device that can exhibit excellent electrochemical characteristics. DETAILED DESCRIPTION
[0031] Hereinafter, embodiments of the present invention will be described in detail.
[0032] Here, the electrochemical element functional layer composition of the present invention (hereinafter also referred to as "functional layer composition") can be used as a material for forming the electrochemical element functional layer of the present invention (hereinafter also referred to as "functional layer"). Moreover, the electrochemical element functional layer of the present invention is formed using the electrochemical element functional layer composition of the present invention. In addition, the electrochemical element of the present invention is an electrochemical element having at least the electrochemical element functional layer of the present invention.
[0033] (Composition for electrochemical element functional layer)
[0034] The electrochemical element functional layer composition of the present invention contains a specified particulate polymer, a binder and inorganic particles, and may also contain other components arbitrarily. Moreover, by using the functional layer composition of the present invention, an electrochemical element functional layer can be formed that can suppress powder loss and can exhibit excellent adhesion while ensuring sufficient heat resistance.
[0035] <Particle-like polymer>
[0036] The granular polymer contained in the composition for functional layer is a polymer having a predetermined average circularity and a predetermined volume average particle diameter as described below, and having a granular shape in the composition for functional layer. In addition, the granular polymer may be granular or in any other shape after the components are bonded to each other via the functional layer formed using the composition for functional layer. Furthermore, the granular polymer may be a crystalline polymer, a non-crystalline polymer, or a mixture thereof.
[0037] <<Average circularity of granular polymer>>
[0038] Furthermore, the average circularity of the granular polymer needs to be 0.90 or more, preferably 0.94 or more, and needs to be less than 0.99, preferably 0.98 or less. By making the average circularity of the granular polymer above the above lower limit, since the number of bonding points between the granular polymer and the inorganic particles in the functional layer formed using the functional layer composition increases, powder loss can be suppressed. On the other hand, by making the average circularity of the granular polymer below the above upper limit, since the state of the granular polymer in the functional layer is stable, powder loss can be suppressed.
[0039] <<Volume Average Particle Diameter of Granular Polymer>>
[0040] In addition, the volume average particle size of the granular polymer needs to be 1.0 μm or more, preferably 1.5 μm or more, more preferably 2.0 μm or more, further preferably 3.0 μm or more, and most preferably more than 5.0 μm, and needs to be 10.0 μm or less, preferably 9.0 μm or less, and more preferably 8.0 μm or less. By making the volume average particle size of the granular polymer above the above lower limit, since the granular polymer is easy to protrude relative to the inorganic particles on the thickness direction surface of the functional layer formed using the functional layer composition, better adhesion can be obtained. And the heat resistance of the functional layer formed using the functional layer composition is improved. On the other hand, by making the volume average particle size of the granular polymer below the above upper limit, it is possible to suppress the granular polymer from falling off when the functional layer composition is applied to the substrate, and form a uniform functional layer. And because the number of granular polymers per unit area of the functional layer increases, the bonding points between the adherend and the functional layer become more, and the bonding strength becomes higher. Here, the reason for the improvement of the heat resistance of the functional layer as described above is not clear, but it can be inferred as follows. That is, in order to improve the heat resistance of the functional layer, the ratio of inorganic particles in the functional layer needs to be high. And it is believed that on the thickness direction surface of the functional layer, by making the granular polymer protrude relative to the inorganic particles, the ratio of inorganic particles in the inorganic particle layer constituting the functional layer in appearance becomes higher, so the heat resistance becomes higher. In addition, it is believed that the heat shrinkage of the functional layer is suppressed by the inorganic particles present around the granular polymer in the inorganic particle layer. And it can be inferred that by making the volume average particle diameter of the granular polymer below the above-mentioned upper limit, the inorganic particles can be well balanced and present around the granular polymer in the inorganic particle layer, so the heat shrinkage of the functional layer can be well suppressed. In addition, the above-mentioned inorganic particle layer is described in detail below.
[0041] The volume average particle size of the particulate polymer can be adjusted by the type and amount of the metal hydroxide used when preparing the particulate polymer. The metal hydroxide will be described in detail below.
[0042] <<Particle Size Distribution of Granular Polymer>>
[0043] Moreover, the particle size distribution of the granular polymer is preferably 1.10 or more, more preferably 1.20 or more, preferably 1.50 or less, more preferably 1.40 or less. If the particle size distribution of the granular polymer is above the above lower limit, a functional layer that can follow the expansion and contraction of the electrode, especially the negative electrode, can be formed. On the other hand, if the particle size distribution of the granular polymer is below the above upper limit, when the components are bonded to each other through the functional layer, the electrochemical characteristics of the electrochemical element are improved because the deviation of the thickness of the functional layer after bonding can be reduced. In addition, powdering can be well suppressed.
[0044] <<Glass transition temperature of granular polymer>>
[0045] In addition, the glass transition temperature (Tg) of the granular polymer is preferably 10°C or more, more preferably 20°C or more, further preferably 30°C or more, preferably 90°C or less, more preferably 80°C or less, and further preferably 70°C or less. If the glass transition temperature of the granular polymer is above the above lower limit, it is possible to suppress the occurrence of adhesion of the functional layer, for example, during the storage of an electrochemical element having a functional layer. On the other hand, if the glass transition temperature of the granular polymer is below the above upper limit, good adhesion of the functional layer can be obtained when the components are pressed and bonded to each other through the functional layer.
[0046] <<Melting Point of Granular Polymer>>
[0047] Furthermore, the melting point (Tm) of the particulate polymer is preferably 50° C. or higher, more preferably 100° C. or higher. When the melting point of the particulate polymer is at least the above lower limit, good adhesion of the functional layer can be ensured even when the particulate polymer contains a crystalline high molecular weight polymer.
[0048] When the particulate polymer has both a glass transition temperature and a melting point, the melting point of the particulate polymer is preferably not less than the above lower limit from the viewpoint of further improving the adhesiveness of the functional layer.
[0049] <<Swelling degree of granular polymer in electrolyte>>
[0050] Furthermore, the electrolyte swelling degree of the granular polymer is preferably 1.0 times or more, more preferably 1.2 times or more, further preferably 1.3 times or more, preferably 15 times or less, more preferably 10 times or less, further preferably 7 times or less, and particularly preferably 5 times or less. If the electrolyte swelling degree of the granular polymer is above the above lower limit, the adhesion of the functional layer in the electrolyte can be made strong. On the other hand, if the electrolyte swelling degree of the granular polymer is below the above upper limit, since the resistance of the functional layer in the electrolyte becomes small, the electrochemical characteristics of the electrochemical element having the functional layer can be improved.
[0051] In the present invention, the "electrolyte swelling degree" can be measured by the method described in Examples of the present specification.
[0052] <<Composition of granular polymer>>
[0053] The particulate polymer is not particularly limited as long as at least the average circularity and the volume average particle size are within the above ranges, and for example, a known polymer that can be used as a binder when forming a functional layer can be used.
[0054] Here, as the monomer units constituting the granular polymer, for example, aromatic vinyl monomer units, (meth) acrylate monomer units, fluorine-containing monomer units, etc. can be cited. In addition, in the present invention, "(meth) acrylic acid" means acrylic acid and / or methacrylic acid. And, from the viewpoint of improving the adhesion between the functional layer and the substrate, the granular polymer preferably contains aromatic vinyl monomer units.
[0055] -Aromatic vinyl monomer unit-
[0056] Here, examples of the aromatic vinyl monomer that can form the aromatic vinyl monomer unit are not particularly limited, and examples thereof include styrene, α-methylstyrene, styrenesulfonic acid, butoxystyrene, and vinylnaphthalene. Among them, styrene is preferred.
[0057] These aromatic vinyl monomers may be used alone or in combination of two or more at any ratio.
[0058] Moreover, when making all monomer units in the granular polymer be 100 mass %, the containing ratio of the aromatic vinyl monomer unit in the granular polymer is preferably more than 30 mass %, more preferably more than 60 mass %, preferably below 95 mass %, more preferably below 90 mass %, further preferably below 89.9 mass %. If the containing ratio of the aromatic vinyl monomer unit is above the above lower limit, the elasticity of the granular polymer improves, the intensity of the functional layer obtained can be ensured, and the adhesion of the functional layer to the substrate can be improved. On the other hand, if the containing ratio of the aromatic vinyl monomer unit is below the above upper limit, the flexibility of the granular polymer improves, and the film-forming property of the functional layer composition when drying improves. Therefore, the adhesion of the functional layer to the substrate can be improved.
[0059] In the present invention, the "content ratio of each monomer unit" can be expressed as 1 Determined by nuclear magnetic resonance (NMR) methods such as H-NMR.
[0060] -(Meth)acrylate monomer unit-
[0061] Examples of (meth)acrylate monomers that can form (meth)acrylate monomer units include butyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, and tert-butyl acrylate, octyl acrylates such as pentyl acrylate, hexyl acrylate, heptyl acrylate, and 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, and stearyl acrylate; and butyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, and tert-butyl methacrylate, octyl methacrylates such as pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, and 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, and stearyl methacrylate. Among them, n-butyl acrylate, 2-ethylhexyl acrylate, and methyl methacrylate are preferred, and 2-ethylhexyl acrylate is more preferred.
[0062] In addition, these (meth)acrylate monomers may be used alone or in combination of two or more at any ratio.
[0063] Moreover, when all repeating units of the granular polymer are 100% by mass, the content of the (meth) acrylate monomer units in the granular polymer is preferably 10% by mass or more, preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 64.9% by mass or less. If the content of the (meth) acrylate monomer units is above the above lower limit, the glass transition temperature of the granular polymer can be prevented from being excessively reduced, so that the anti-blocking property of the obtained functional layer is improved. On the other hand, if the content of the (meth) acrylate monomer units is below the above upper limit, the adhesion of the functional layer to the substrate can be made good.
[0064] -Fluorine-containing monomer units-
[0065] Examples of the fluorine-containing monomer that can form the fluorine-containing monomer unit are not particularly limited, and examples thereof include vinylidene fluoride, tetrafluoroethylene, hexafluoropropylene, chlorotrifluoroethylene, vinyl fluoride, and perfluoroalkyl vinyl ether, among which vinylidene fluoride is preferred.
[0066] These fluorine atom-containing monomers may be used alone or in combination of two or more at any ratio.
[0067] Here, in the case where the granular polymer includes a fluorine-containing atom monomer unit, from the viewpoint of being able to ensure the better adhesion of the functional layer, the granular polymer is preferably a fluorine-containing atom polymer using vinylidene fluoride as a fluorine-containing atom monomer. Wherein, as a fluorine-containing atom polymer, preferably (i) a homopolymer of vinylidene fluoride, (ii) a copolymer of vinylidene fluoride and other fluorine-containing atom monomers that can be copolymerized with the vinylidene fluoride, (iii) vinylidene fluoride, other fluorine-containing atom monomers that can be copolymerized with the vinylidene fluoride, and a copolymer of the monomer that can copolymerize with them. And, in fluorine-containing atom polymers, preferably polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), polyvinyl fluoride and tetrafluoroethylene and perfluoroalkyl vinyl ether copolymers.
[0068] Furthermore, the particulate polymer may contain a crosslinkable monomer unit in addition to the above-mentioned monomer units. Here, the crosslinkable monomer unit refers to a monomer that can form a crosslinked structure during or after polymerization by heating or irradiation with energy rays.
[0069] - Cross-linking monomer unit-
[0070] Moreover, as a monomer that can form a crosslinkable monomer unit, for example, a multifunctional monomer having two or more polymerizable reactive groups in the monomer can be cited. As such a multifunctional monomer, for example, divinyl compounds such as allyl methacrylate and divinylbenzene can be cited; di(meth)acrylate compounds such as diethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, 1,3-butanediol diacrylate; tri(meth)acrylate compounds such as trimethylolpropane trimethacrylate and trimethylolpropane triacrylate; ethylenically unsaturated monomers containing epoxy groups such as allyl glycidyl ether and glycidyl methacrylate, etc. Among them, ethylene glycol dimethacrylate is preferred.
[0071] These crosslinkable monomers may be used alone or in combination of two or more at any ratio.
[0072] Furthermore, when the amount of all monomer units of the particulate polymer is 100% by mass, the content of the crosslinkable monomer units in the particulate polymer is preferably 0.02% by mass or more, more preferably 0.1% by mass or more, preferably 2% by mass or less, more preferably 1.5% by mass or less, and further preferably 1% by mass or less. If the content of the crosslinkable monomer units is within the above range, the dissolution of the particulate polymer in the electrolyte can be sufficiently suppressed.
[0073] -Other monomer units-
[0074] Furthermore, the granular polymer may include other monomer units except the aromatic vinyl monomer unit, the (meth)acrylate monomer unit, the fluorine-containing monomer unit and the crosslinking monomer unit. Here, other monomer units are not particularly limited, and for example, nitrile-containing monomer units and acid-containing monomer units described in the "binding material" item described later can be cited.
[0075] -Nitrile-containing monomer unit-
[0076] Here, as an example of a nitrile group-containing monomer that can form a nitrile group-containing monomer unit, an α,β-ethylenically unsaturated nitrile monomer can be cited. Specifically, as the α,β-ethylenically unsaturated nitrile monomer, there is no particular limitation as long as it is an α,β-ethylenically unsaturated compound having a nitrile group, and examples thereof include acrylonitrile; α-halogenated acrylonitrile such as α-chloroacrylonitrile and α-bromoacrylonitrile; α-alkyl acrylonitrile such as methacrylonitrile and α-ethylacrylonitrile, and the like.
[0077] These nitrile group-containing monomers may be used alone or in combination of two or more at any ratio.
[0078] Moreover, when all repeating units in the granular polymer are 100% by mass, the content of the nitrile-containing monomeric unit in the granular polymer is preferably more than 3% by mass, more preferably more than 4% by mass, more preferably more than 6% by mass, preferably less than 30% by mass, more preferably less than 27% by mass, more preferably less than 25% by mass. If the content of the nitrile-containing monomeric unit is above the above lower limit, the cohesive force of the granular polymer can be improved and the peel strength of the functional layer can be improved. On the other hand, if the content of the nitrile-containing monomeric unit is below the above upper limit, the flexibility of the granular polymer can be improved.
[0079] Furthermore, the content of other monomer units other than the nitrile group-containing monomer units in the particulate polymer is preferably 0% by mass or more, preferably 10% by mass or less, more preferably 7% by mass or less, and further preferably 5% by mass or less. If the content of other monomer units is 10% by mass or less, the stability of the composition for the functional layer can be suppressed from decreasing.
[0080] The content of the particulate polymer in the functional layer composition is preferably 1% by mass or more and 12% by mass or less relative to the total amount (100% by mass) of the particulate polymer, the binder, and the inorganic particles.
[0081] [Preparation of granular polymer]
[0082] The particulate polymer can be prepared by polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. Here, the ratio of each monomer in the monomer composition is usually the same as the ratio of each monomer unit in the particulate polymer.
[0083] Furthermore, the polymerization method is not particularly limited, and any method such as suspension polymerization, emulsion polymerization coagulation method, pulverization method, etc. can be used. Among them, from the viewpoint of easily adjusting the granular polymer to the specific average circularity specified in the present invention, suspension polymerization and emulsion polymerization coagulation method are preferred, and suspension polymerization method is more preferred. In addition, as the polymerization reaction, any reaction such as free radical polymerization and living free radical polymerization can be used.
[0084] [Other compounding ingredients]
[0085] Furthermore, other compounding agents such as a chain transfer agent, a polymerization regulator, a polymerization reaction retarder, a reactive fluidizing agent, a filler, a flame retardant, an anti-aging agent, a coloring agent, etc. may be compounded in any amount into the monomer composition used for preparing the particulate polymer.
[0086] Here, as an example, a method for producing a particulate polymer by a suspension polymerization method will be described.
[0087] [Preparation of granular polymer by suspension polymerization]
[0088] (1) Preparation of monomer composition
[0089] First, monomers constituting a desired particulate polymer and other compounding agents added as necessary are mixed to prepare a monomer composition.
[0090] (2) Droplet formation
[0091] Next, the monomer composition is dispersed in water, and a polymerization initiator is added to form droplets of the monomer composition. The method for forming the droplets is not particularly limited, and the droplets can be formed by shearing and stirring water containing the monomer composition using a disperser such as an emulsifying disperser.
[0092] At this time, as the polymerization initiator used, for example, oil-soluble polymerization initiators such as tert-butyl peroxy-2-ethylhexanoate and azobisisobutyronitrile can be mentioned. In addition, the polymerization initiator can be added after the monomer composition is dispersed in water and before droplets are formed, or it can be added to the monomer composition before it is dispersed in water.
[0093] Furthermore, from the viewpoint of stabilizing the formed monomer composition droplets in water, it is preferred to add a dispersion stabilizer to water to form the monomer composition droplets. In this case, as the dispersion stabilizer, for example, metal hydroxides such as magnesium hydroxide, sodium dodecylbenzenesulfonate, etc. can be used.
[0094] (3) Aggregation
[0095] After the droplets of the monomer composition are formed, the water containing the formed droplets is heated to initiate polymerization, thereby forming a particulate polymer in the water. At this time, the polymerization reaction temperature is preferably 50° C. or higher and 95° C. or lower. In addition, the polymerization reaction time is preferably 1 hour or higher and 10 hours or lower, preferably 8 hours or lower, and more preferably 6 hours or lower.
[0096] (4) Cleaning, filtering, dehydration and drying processes
[0097] After the polymerization is completed, the water containing the particulate polymer is washed, filtered, and dried according to a conventional method, thereby obtaining the particulate polymer.
[0098] <Bonding material>
[0099] The binder contained in the composition for a functional layer can be used to prevent components such as a particulate polymer contained in the functional layer formed using the composition for a functional layer of the present invention from falling out of the functional layer.
[0100] Moreover, the binding material is not particularly limited, and can include known polymers that are non-water-soluble and can be dispersed in a dispersion medium such as water, for example, binding resins such as thermoplastic elastomers. Moreover, as the thermoplastic elastomer, conjugated diene polymers and acrylic polymers are preferred, and acrylic polymers are more preferred.
[0101] Here, conjugated diene polymer refers to a polymer comprising a conjugated diene monomer unit. Moreover, as a specific example of a conjugated diene polymer, there is no particular limitation, and examples thereof include copolymers comprising aromatic vinyl monomer units and aliphatic conjugated diene monomer units, butadiene rubber (BR), acrylonitrile-butadiene rubber (NBR) (comprising a copolymer of acrylonitrile units and butadiene units) and their hydrides, etc., such as styrene-butadiene copolymers (SBR).
[0102] In addition, an acrylic polymer refers to a polymer containing a (meth)acrylic acid ester monomer unit.
[0103] These binders may be used alone or in combination of two or more at any ratio.
[0104] Furthermore, examples of acrylic polymers that can be preferably used as the binder include, but are not particularly limited to, polymers containing the above-mentioned (meth)acrylic acid ester monomer units, crosslinkable monomer units, and acid group-containing monomer units described below.
[0105] -Acid group-containing monomer unit-
[0106] Here, examples of the acid group-containing monomer that can form the acid group-containing monomer unit include monomers having a carboxylic acid group, monomers having a sulfonic acid group, monomers having a phosphoric acid group, and monomers having a hydroxyl group.
[0107] Examples of the monomer having a carboxylic acid group include monocarboxylic acids and dicarboxylic acids. Examples of the monocarboxylic acids include acrylic acid, methacrylic acid, and crotonic acid. Examples of the dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid.
[0108] Examples of the monomer having a sulfonic acid group include vinyl sulfonic acid, methylvinyl sulfonic acid, (meth)allyl sulfonic acid, ethyl (meth)acrylate-2-sulfonate, 2-acrylamide-2-methylpropanesulfonic acid, and 3-aryloxy-2-hydroxypropanesulfonic acid.
[0109] In addition, in this specification, "(meth)allyl" means allyl and / or methallyl, and (meth)acrylic acid means acrylic acid and / or methacrylic acid.
[0110] Furthermore, examples of the monomer having a phosphoric acid group include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate.
[0111] In addition, in this specification, "(meth)acryloyl group" means an acryloyl group and / or a methacryloyl group.
[0112] Moreover, as a monomer which has a hydroxyl group, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, etc. are mentioned, for example.
[0113] These acid group-containing monomers may be used alone or in combination of two or more at any ratio.
[0114] In addition, the ratio of the (meth) acrylate monomer unit in the acrylic polymer is preferably 50% by mass or more, more preferably 55% by mass or more, further preferably 58% by mass or more, preferably 98% by mass or less, more preferably 97% by mass or less, and further preferably 96% by mass or less. By making the ratio of the (meth) acrylate monomer unit above the above lower limit, the peel strength of the functional layer can be further improved. In addition, by making the ratio of the (meth) acrylate monomer unit below the above upper limit, the electrochemical characteristics of the electrochemical element with the functional layer can be further improved.
[0115] In addition, the ratio of the crosslinkable monomer unit in the acrylic polymer is preferably 0.1% by mass or more, more preferably 1.0% by mass or more, preferably 3.0% by mass or less, more preferably 2.5% by mass or less. By making the ratio of the crosslinkable monomer unit above the above lower limit, the electrochemical properties of the electrochemical element with the functional layer can be further improved. In addition, by making the ratio of the crosslinkable monomer unit below the above upper limit, the peel strength of the functional layer can be further improved.
[0116] Moreover, the ratio of the acid-containing monomer units in the acrylic polymer is preferably 0.1% by mass or more, more preferably 0.3% by mass or more, further preferably 0.5% by mass or more, preferably 20% by mass or less, more preferably 10% by mass or less, further preferably 5% by mass or less. By making the ratio of the acid-containing monomer units above the above lower limit, the dispersibility of the binding material in the functional layer composition and in the functional layer can be improved, and the electrochemical characteristics of the electrochemical element with the functional layer can be fully improved. In addition, by making the ratio of the acid-containing monomer units below the above upper limit, the residual moisture content of the functional layer can be reduced, and the electrochemical characteristics of the electrochemical element can be fully improved.
[0117] Furthermore, the acrylic polymer may also contain other monomer units. Moreover, as other monomers that can form other monomer units that can be contained in the acrylic polymer, there can be cited aliphatic conjugated diene monomers such as 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, and 2-chloro-1,3-butadiene; aromatic vinyl monomers and nitrile-containing monomers, ethylene, propylene and other olefin monomers described in the "composition of the granular polymer"; halogen atom-containing monomers such as vinyl chloride and vinylidene chloride; vinyl ester monomers such as vinyl acetate, vinyl propionate, vinyl butyrate, and vinyl benzoate; vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, and butyl vinyl ether; vinyl ketone monomers such as methyl vinyl ketone, ethyl vinyl ketone, butyl vinyl ketone, hexyl vinyl ketone, and isopropenyl vinyl ketone; and heterocyclic vinyl compound monomers such as N-vinyl pyrrolidone, vinyl pyridine, and vinyl imidazole. Among them, as other monomers, acrylonitrile is preferred.
[0118] These other monomers may be used alone or in combination of two or more at any ratio. The content ratio of the other monomer units in the acrylic polymer may be adjusted appropriately.
[0119] <<Glass transition temperature of adhesive material>>
[0120] Moreover, the glass transition temperature (Tg) of the adhesive material is preferably above -100°C, more preferably above -90°C, further preferably above -80°C, preferably less than 30°C, more preferably below 20°C, further preferably below 15°C. If the glass transition temperature of the adhesive material is above the above lower limit, the adhesiveness and strength of the adhesive material can be improved. On the other hand, if the glass transition temperature of the adhesive material is below the above upper limit, the flexibility of the functional layer can be further improved.
[0121] <<Volume average particle size of the binder>>
[0122] In addition, the volume average particle size of the binding material is preferably 0.1 μm or more, preferably 0.4 μm or less. If the volume average particle size of the binding material is above the above lower limit, the ion conductivity in the functional layer can be further suppressed, and the electrochemical properties (especially output properties) of the electrochemical element can be improved. On the other hand, if the volume average particle size of the binding material is below the above upper limit, the peel strength of the functional layer can be fully improved.
[0123] The volume average particle size of the binder can be measured by the method described in Examples of the present specification.
[0124] [Content of bonding material]
[0125] Moreover, the content of the binding material in the functional layer is preferably 0.1 mass parts or more, more preferably 0.2 mass parts or more, more preferably 0.5 mass parts or more, preferably 20 mass parts or less, more preferably 15 mass parts or less, and more preferably 10 mass parts or less relative to the total of 100 mass parts of inorganic particles and granular polymers. If the content of the binding material in the functional layer is above the above lower limit, the granular polymer can be fully prevented from falling off from the functional layer, and the peel strength of the functional layer can be fully improved. On the other hand, if the content of the binding material in the functional layer is below the above upper limit, the ionic conductivity of the functional layer can be suppressed to decrease, and the electrochemical characteristics of the electrochemical element can be suppressed to decrease.
[0126] The binder is not particularly limited and can be prepared by, for example, polymerizing a monomer composition containing the above-mentioned monomers in an aqueous solvent such as water. Here, the ratio of each monomer in the monomer composition is usually the same as the ratio of each monomer unit in the binder.
[0127] The polymerization method and the polymerization reaction are not particularly limited, and for example, the polymerization method and the polymerization reaction exemplified in the polymerization method of the above-mentioned particulate polymer can be used.
[0128] The binder may be in a granular or non-granular shape, but is preferably in a granular shape from the viewpoint of satisfactorily suppressing the components included in the functional layer from falling out.
[0129] <Inorganic particles>
[0130] The inorganic particles contained in the composition for the functional layer can generally improve the heat resistance of the functional layer. Here, the material of the inorganic particles is preferably stable in the use environment of the electrochemical element and electrochemically stable. From this point of view, the preferred materials for the inorganic particles include aluminum oxide (alumina), aluminum oxide hydrate (boehmite (AlOOH)), gibbsite (Al(OH 3 )), silicon oxide, magnesium oxide (Magnesia), magnesium hydroxide, calcium oxide, titanium dioxide (Titania), barium titanate (BaTiO 3 ), zirconium oxide (ZrO), aluminum oxide-silicon dioxide composite oxide and other oxide particles; aluminum nitride, boron nitride and other nitride particles; covalent crystal particles such as silicon and diamond; barium sulfate, calcium fluoride, barium fluoride and other insoluble ion crystal particles; talc, montmorillonite and other clay particles. Among these, aluminum oxide, aluminum oxide hydrate (boehmite), titanium oxide and barium sulfate are more preferred, and aluminum oxide is further preferred. In addition, these particles can be subjected to element replacement, surface treatment, solid solution, etc. as needed.
[0131] These inorganic particles may be used alone or in combination of two or more at any ratio.
[0132] <Volume Average Particle Diameter of Inorganic Particles>
[0133] Moreover, the volume average particle size (D50) of the inorganic particles is preferably 0.1 μm or more, more preferably 0.2 μm or more, further preferably 0.3 μm or more, preferably 1 μm or less, more preferably 0.9 μm or less, and further preferably 0.8 μm or less. If the volume average particle size of the inorganic particles is above the above lower limit, the inorganic particles can be tightly packed in the functional layer. Therefore, the reduction of ion conductivity in the functional layer can be further suppressed, and the electrochemical characteristics (especially output characteristics) of the electrochemical element can be improved. In addition, if the volume average particle size of the inorganic particles is below the above upper limit, even if the functional layer is thin, the functional layer can exert excellent heat resistance, so the capacity of the electrochemical element can be increased.
[0134] <Mixing ratio of inorganic particles and particulate polymer>
[0135] Furthermore, the mixing ratio of the inorganic particles and the particulate polymer in the composition for the functional layer is preferably 95:5 to 55:45, more preferably 80:20 to 55:45, further preferably 75:25 to 60:40, and particularly preferably 70:30 to 65:35, by volume ratio (inorganic particles: particulate polymer). If the mixing ratio of the inorganic particles and the particulate polymer is within the above range by volume ratio, the balance between heat resistance and adhesiveness of the functional layer is good.
[0136] In addition, the mixing ratio of the inorganic particles and the particulate polymer in the composition for the functional layer is preferably 49:51 to 99:1, more preferably 58:42 to 94:6, and further preferably 64:39 to 91:9, in terms of mass ratio (inorganic particles: particulate polymer). If the mixing ratio of the inorganic particles and the particulate polymer is within the above range in terms of mass ratio, the balance between the heat resistance and the adhesiveness of the functional layer is further improved.
[0137] <Other ingredients>
[0138] The composition for the functional layer may contain any other components in addition to the above components. The other components are not particularly limited as long as they do not affect the electrochemical reaction in the electrochemical element, and examples thereof include known additives such as dispersants, viscosity modifiers, and wetting agents. These other components may be used alone or in combination of two or more.
[0139] <Method for preparing composition for electrochemical element functional layer>
[0140] The preparation method of the functional layer composition is not particularly limited, and can be prepared by, for example, mixing the above-mentioned granular polymer, binding material, inorganic particles, water as a dispersion medium, and other components used as needed. In addition, in an aqueous solvent, when the monomer composition is polymerized to prepare a granular polymer and a binding material, the granular polymer and the binding material can be directly mixed with other components in the state of an aqueous dispersion. In addition, when the granular polymer and the binding material are mixed in the state of an aqueous dispersion, the water in the aqueous dispersion can be used as a dispersion medium.
[0141] Here, the mixing method of the above-mentioned components is not particularly limited. In order to disperse the components more efficiently, it is preferred to use a disperser as a mixing device for mixing. Moreover, the disperser is preferably a device that can evenly disperse and mix the above-mentioned components. As the disperser, a ball mill, a sand mill, a pigment disperser, a grinder, an ultrasonic disperser, a homogenizer, a planetary mixer, etc. can be cited.
[0142] (Functional layer for electrochemical device)
[0143] The functional layer for electrochemical element can be formed on, for example, a suitable substrate using the above-mentioned functional layer composition. Here, the functional layer at least comprises the above-mentioned granular polymer, a binding material, inorganic particles, and other components used as needed. In addition, each component included in the functional layer is each component included in the above-mentioned functional layer composition, and the preferred existence ratio of these components is the same as the preferred existence ratio of each component in the functional layer composition.
[0144] Here, the method for forming the functional layer on the substrate using the composition for a functional layer is not particularly limited, and examples thereof include the following methods.
[0145] 1) A method of applying a functional layer composition to the surface of a substrate and then drying the composition
[0146] 2) A method of dipping a substrate in a composition for a functional layer and then drying the substrate
[0147] 3) A method of applying a composition for a functional layer on a release substrate, drying the composition to form a functional layer, and transferring the obtained functional layer to the surface of the substrate
[0148] In addition, the functional layer may be formed on only one side of the substrate, or may be formed on both sides of the substrate.
[0149] Among these, the method 1) is preferred because the thickness of the functional layer can be easily controlled. Furthermore, the method 1) may include, for example, a step of applying the composition for a functional layer on a substrate (coating step) and a step of drying the composition for a functional layer applied on the substrate to form a functional layer (functional layer forming step).
[0150] [Coating process]
[0151] In the coating step, the method for coating the functional layer composition on the substrate is not particularly limited, and examples thereof include doctor blade method, reverse roll method, direct roll method, gravure printing method, extrusion method, brush coating method and the like.
[0152] [Functional layer forming step]
[0153] In addition, in the functional layer forming step, the method for drying the functional layer composition on the substrate is not particularly limited, and a known method can be used, for example, drying using warm air, hot air, or low-humidity air; vacuum drying; and drying using irradiation with infrared rays, electron beams, etc. There are no particular limitations on the drying conditions, but the drying temperature is preferably 50 to 150° C., and the drying time is preferably 1 to 30 minutes.
[0154] Furthermore, the functional layer formed on the substrate can be preferably used as a single layer that simultaneously functions as a heat-resistant layer for improving the heat resistance of the substrate and as an adhesive layer for firmly bonding members to each other.
[0155] In addition, a substrate having a functional layer formed using a functional layer composition as described above (hereinafter also referred to as a "functional layer substrate") can be produced in shorter working hours and time than a conventional substrate having a heat-resistant layer and an adhesive layer, and therefore has high productivity.
[0156] Here, in the functional layer formed using the functional layer composition, a plurality of inorganic particles are usually arranged in an overlapping manner along the thickness direction of the functional layer. Moreover, the thickness of the layer formed by overlapping inorganic particles along the thickness direction of the functional layer (hereinafter also referred to as "inorganic particle layer") is preferably 0.5 μm or more, more preferably 0.8 μm or more, more preferably 1 μm or more, preferably 6 μm or less, more preferably 5 μm or less, and more preferably 4 μm or less. If the thickness of the inorganic particle layer is above the above lower limit, the heat resistance of the functional layer is extremely good. On the other hand, if the thickness of the inorganic particle layer is below the above upper limit, the ion diffusivity of the functional layer can be ensured, and the electrochemical characteristics (output characteristics) of the electrochemical element can be further fully improved.
[0157] [Ratio of volume average particle size of particulate polymer to thickness of inorganic particle layer]
[0158] In addition, the ratio of the volume average particle size of the granular polymer to the thickness of the above-mentioned inorganic particle layer (volume average particle size of the granular polymer / thickness of the inorganic particle layer) is preferably 0.75 or more, more preferably 1.0 or more, further preferably 1.5 or more, preferably 5.0 or less, more preferably 3.0 or less. If the ratio of the volume average particle size of the granular polymer to the thickness of the inorganic particle layer is above the above lower limit, the granular polymer is more likely to protrude relative to the surface of the inorganic particles on the thickness direction surface of the functional layer, so better adhesion can be exerted. In addition, if the ratio of the volume average particle size of the granular polymer to the thickness of the inorganic particle layer is above the above lower limit, the granular polymer can be further suppressed from falling off when the functional layer composition is applied to the substrate, forming a more uniform functional layer.
[0159] [Maximum thickness of functional layer]
[0160] Furthermore, the maximum thickness of the functional layer formed on the substrate is preferably 1.0 μm or more, more preferably 1.5 μm or more, more preferably 2.0 μm or more, particularly preferably 2.5 μm or more, most preferably 5.0 μm or more, preferably 10.0 μm or less, more preferably 9.0 μm or less, and more preferably 8.0 μm or less. That is, in the functional layer formed, it is preferred that the inorganic particle layer and the granular polymer do not overlap each other in the thickness direction of the functional layer, and the thickness of the functional layer is equal to the volume average particle size of the granular polymer contained in the functional layer. Moreover, if the maximum thickness of the functional layer is above the above lower limit, the heat resistance of the functional layer is extremely good. On the other hand, if the maximum thickness of the functional layer is below the above upper limit, the ion diffusivity of the functional layer can be ensured, and the electrochemical characteristics (output characteristics) of the electrochemical element can be further fully improved.
[0161] In addition, in this specification, "the maximum thickness of the functional layer" can be measured using, for example, a field emission scanning electron microscope (FE-SEM).
[0162] (Electrochemical Components)
[0163] The electrochemical device having the functional layer of the present invention only needs to have at least the functional layer of the present invention, and therefore may have constituent elements other than the functional layer of the present invention unless the effects of the present invention are significantly impaired.
[0164] Furthermore, the electrochemical device of the present invention is not particularly limited, and may be, for example, a lithium ion secondary battery or an electric double layer capacitor, and is preferably a lithium ion secondary battery.
[0165] Here, a lithium ion secondary battery as an example of an electrochemical element of the present invention is described below. The lithium ion secondary battery of the present invention has the functional layer of the present invention described above. More specifically, the lithium ion secondary battery has a positive electrode, a negative electrode, a separator (a separator with a functional layer) formed on a separator substrate and an electrolyte. In addition, the functional layer can be formed only on a single side of the separator substrate, or on both sides of the separator substrate.
[0166] Moreover, in the lithium ion secondary battery of the present invention, the positive electrode and the separator substrate and / or the negative electrode and the separator substrate are firmly bonded in the electrolyte through the functional layer. Therefore, it is possible to suppress the distance between the electrode plates from expanding with repeated charge and discharge, so that the battery characteristics such as cycle characteristics are good. In addition, in the lithium ion secondary battery, the heat resistance of the separator substrate is improved by the functional layer. Furthermore, compared with the case where an existing separator with a heat-resistant layer and an adhesive layer is used, the lithium ion secondary battery can shorten the time required to manufacture the separator, and can manufacture the separator with high productivity.
[0167] In addition, as the above-mentioned positive electrode, negative electrode, and electrolyte solution, known positive electrode, negative electrode, and electrolyte solution used in lithium ion secondary batteries can be used.
[0168] <Positive and negative electrodes>
[0169] Specifically, as an electrode (positive electrode and negative electrode), an electrode formed by forming an electrode composite material layer on a current collector can be used. In addition, as a current collector, a current collector formed of metal materials such as iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. Among these, as a current collector for the negative electrode, a current collector formed of copper is preferably used. In addition, as a current collector for the positive electrode, a current collector formed of aluminum is preferably used. Furthermore, as an electrode composite material layer, a layer comprising an electrode active material and a binder can be used.
[0170] <Spacer with functional layer>
[0171] The separator with a functional layer can be produced by forming a functional layer on a separator substrate using, for example, the method for forming a functional layer listed in the above section "Functional layer for electrochemical device".
[0172] Here, the separator substrate is not particularly limited, and for example, the separator substrate described in Japanese Patent Publication No. 2012-204303 can be used. Among these, from the viewpoint of being able to make the overall film thickness of the functional layer separator thinner, thereby increasing the ratio of the electrode active material in the lithium ion secondary battery and increasing the capacity per unit volume, a microporous membrane formed of a polyolefin resin (polyethylene, polypropylene, polybutylene, polyvinyl chloride) is preferred.
[0173] <Electrolyte>
[0174] As the electrolyte, an organic electrolyte prepared by dissolving a supporting electrolyte in an organic solvent is generally used. As the supporting electrolyte, for example, in a lithium ion secondary battery, a lithium salt can be used. Examples of the lithium salt include LiPF 6 、LiAsF 6 , LiBF 4 、LiSbF 6 、LiAlCl 4 、LiClO 4 CF 3 SO 3 Li, C 4 F 9 SO 3 Li, CF 3 COOLi, (CF 3 CO) 2 NLi, (CF 3 SO 2 ) 2 NLi, (C2 F 5 SO 2 Among them, LiPF is preferred because it is easily dissolved in a solvent and exhibits a high degree of dissociation. 6 、LiClO 4 CF 3 SO 3 Li. In addition, the electrolyte may be used alone or in combination of two or more. Generally, the lithium ion conductivity tends to be higher when a supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted according to the type of supporting electrolyte.
[0175] The organic solvent used in the electrolyte is not particularly limited as long as it can dissolve the supporting electrolyte. For example, in lithium-ion secondary batteries, it is preferred to use carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (ethyl methyl carbonate (EMC)), and vinylene carbonate; esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as cyclopentane and dimethyl sulfoxide, etc.
[0176] In addition, a mixed solution of these organic solvents can also be used. Among them, carbonates are preferred from the perspective of high dielectric constant and wide stable potential region. Generally, the lower the viscosity of the organic solvent used, the higher the lithium ion conductivity tends to be, so the lithium ion conductivity can be adjusted according to the type of organic solvent.
[0177] The concentration of the electrolyte in the electrolytic solution can be adjusted appropriately. In addition, a known additive can be added to the electrolytic solution.
[0178] <Method for producing lithium-ion secondary battery>
[0179] The lithium-ion secondary battery as the electrochemical element of the present invention can be manufactured by, for example, the following method: overlap the above-mentioned positive electrode and negative electrode through a functional layer separator, wind and bend them as needed and put them into a battery container, inject electrolyte into the battery container and seal it. Here, metal mesh, fuse, PTC element and other overcurrent protection elements, guide plates, etc. can be placed in the battery container as needed to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be, for example, any of coin-shaped, button-shaped, sheet-shaped, cylindrical, square, flat, etc.
[0180] Example
[0181] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0182] Furthermore, unless otherwise stated, in a polymer produced by copolymerizing a plurality of monomers, the proportion of a structural unit formed by polymerizing a certain monomer in the above polymer is generally consistent with the ratio (feed ratio) of the certain monomer in all monomers used to polymerize the polymer.
[0183] In the embodiments and comparative examples, the glass transition temperature, volume average particle size, particle size distribution, electrolyte swelling degree, average circularity, thickness of the inorganic particle layer, and the mixing ratio of the inorganic particles and the granular polymer were measured by the following method. In addition, process adhesion, anti-blocking property of the functional layer, heat resistance of the functional layer, electrolyte injection property, cycle characteristics of the secondary battery, output characteristics of the secondary battery, and resistance to powdering of the functional layer were measured and evaluated by the following method.
[0184] <Glass transition temperature>
[0185] The granular polymer and the binder prepared in the examples and comparative examples were used as the test samples. 10 mg of the test sample was weighed in an aluminum pan, and the test was carried out using a differential thermal analysis measuring device ("EXSTARDSC6220" manufactured by SII NanoTechnology Inc.) with an empty aluminum pan as a reference, in the test temperature range of -100°C to 500°C at a heating rate of 10°C / min, under the conditions specified in JIS Z8703, to obtain a differential scanning calorimetry (DSC) curve. During the heating process, the intersection of the baseline immediately before the endothermic peak of the DSC curve where the differential signal (DDSC) becomes 0.05 mW / min / mg or more and the tangent line of the DSC curve at the first inflection point after the endothermic peak was determined as the glass transition temperature (°C).
[0186] <Volume Average Particle Size>
[0187] <<Volume Average Particle Size and Particle Size Distribution of Granular Polymer>>
[0188] The granular polymer prepared in the examples and comparative examples was used as a measurement sample. 0.1 g of the measurement sample was weighed and placed in a beaker, and 0.1 mL of an alkylbenzenesulfonic acid aqueous solution (manufactured by FUJIFILM Corporation, "DRIWEL") was added as a dispersant. 10 to 30 mL of a diluent (manufactured by Beckman Coulter, "isotone.II") was further added to the above beaker, and dispersed for 3 minutes using a 20 W (Watt) ultrasonic disperser. Then, using a particle size measuring machine (manufactured by Beckman Coulter, "Multisizer"), the volume average particle size (Dv) of the measurement sample was measured under the conditions of pore size: 20 μm, medium: isotone.II, and number of particles to be measured: 100,000. In addition, the number average particle size (Dn) of the granular polymer was also measured, and the particle size distribution (Dv / Dn) was calculated.
[0189] <<Volume average particle size of the binder>>
[0190] The volume average particle size of the adhesive material prepared in the embodiment is measured by laser diffraction. Specifically, an aqueous dispersion solution (adjusted to a solid content concentration of 0.1% by mass) containing the prepared adhesive material is used as a sample. Then, a laser diffraction particle size distribution measuring device (Beckman Coulter, "LS-230") is used to measure the particle size distribution (volume basis), and in the measured particle size distribution, the particle size D50 at which the cumulative volume calculated from the small diameter side becomes 50% is used as the volume average particle size.
[0191] <Electrolyte swelling degree>
[0192] The aqueous dispersion containing the granular polymer prepared in the examples and comparative examples was added to a petri dish made of polytetrafluoroethylene and dried at 25°C for 48 hours to prepare a powder. About 0.2 g of the obtained powder was pressed at 200°C and 5 MPa for 2 minutes to obtain a film. The obtained film was then cut into 1 cm squares to obtain test pieces. The mass W0 of the test piece was measured.
[0193] Furthermore, the test piece was immersed in the electrolyte at 60° C. for 72 hours. Then, the test piece was taken out from the electrolyte, the electrolyte on the surface of the test piece was wiped off, and the mass W1 of the test piece after immersion was measured.
[0194] Using the measured masses W0 and W1, the electrolyte swelling degree S (times) is calculated by S=W1 / W0.
[0195] In addition, as the electrolyte, LiPF as a supporting electrolyte was dissolved in a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and vinylene carbonate (VC) (volume ratio: EC / DEC / VC=68.5 / 30 / 1.5) at a concentration of 1 mol / L. 6 The electrolyte formed.
[0196] <Average roundness>
[0197] The granular polymer prepared in the examples and comparative examples is used as a measurement sample. 10 mL of ion exchange water is pre-added in a container, 0.02 g of a surfactant (alkylbenzene sulfonic acid) as a dispersant is added thereto, and then 0.02 g of the measurement sample is added, and an ultrasonic disperser is used to perform a dispersion treatment at 60 W (Watt) for 3 minutes. The concentration of the measurement sample during the measurement is adjusted to 3000 to 10000 pieces / μL, and a flow particle image analyzer (Sysmex Corporation, "FPIA-3000") is used to measure 1000 to 10000 measurement samples with an equivalent circle diameter of 0.4 μm or more. In addition, the roundness is as shown in the following formula (I), and the average roundness is taken as the average value.
[0198] Circularity = circumference of a circle equal to the projected area of the granular polymer / circumference of the projected image of the granular polymer (I)
[0199] <Thickness of Inorganic Particle Layer>
[0200] The cross section of the functional layer spacer was observed using a field emission scanning electron microscope (FE-SEM), and the thickness of the inorganic particle layer was calculated based on the image obtained. In addition, the thickness of the inorganic particle layer is the distance in the vertical direction from the surface of the spacer on the functional layer side to the inorganic particles on the functional layer surface.
[0201] <Mixing ratio of inorganic particles and particulate polymer>
[0202] The mixing ratio (volume ratio) of the inorganic particles (alumina) and the granular polymer was calculated based on the feeding amount of the inorganic particles (alumina) and the granular polymer when preparing the slurry composition. In addition, the density of alumina was calculated to be 4 g / cm 3 .
[0203] <Process Adhesion>
[0204] The positive electrode and the functional layer separator prepared in the embodiment and the comparative example were cut into pieces with a width of 10 mm and a length of 50 mm, respectively, and the positive electrode and the functional layer separator were stacked and pressed using a roller press at a temperature of 70°C, a load of 10 kN / m, and a pressing speed of 30 m / min to obtain an integrated product in which the positive electrode and the functional layer separator are integrated.
[0205] The obtained integrated product is placed with the current collector side of the positive electrode facing downward, and a transparent tape is pasted on the surface of the positive electrode. At this time, the transparent tape specified in JIS Z1522 is used as the transparent tape. In addition, the transparent tape is pre-fixed on a horizontal test bench. Then, one end of the functional layer spacer is stretched vertically upward at a stretching speed of 50 mm / min, and the stress during peeling is measured.
[0206] In addition, the negative electrodes prepared in the examples and comparative examples were also subjected to stress measurement by the same operation as in the case of using the positive electrode.
[0207] The stress was measured three times for each of the integrated product of the positive electrode and the functional layer separator and the integrated product of the negative electrode and the functional layer separator, for a total of six times, and the average stress was calculated and used as the peel strength (N / m).
[0208] Then, the calculated peel strength was used to evaluate the process adhesion between the electrode and the separator with a functional layer according to the following criteria: A larger peel strength indicates higher process adhesion (adhesion of battery components in the battery manufacturing process).
[0209] A: Peel strength is 3N / m or more
[0210] B: Peel strength is 2 N / m or more and less than 3 N / m
[0211] C: Peel strength is 1 N / m or more and less than 2 N / m
[0212] D: Peel strength less than 1N / m
[0213] <Anti-blocking properties of functional layer>
[0214] The functional layer spacer produced in the embodiment and the comparative example is cut into two pieces of 4 cm wide × 4 cm long as test pieces. After overlapping the two test pieces obtained in a manner that the functional layer sides are opposite to each other, they are pressed for 2 minutes at a temperature of 40°C and a pressure of 5MPa to obtain a pressed body. One end of the obtained pressed body is fixed, and the other end of the pressed body is stretched vertically upward at a tensile speed of 50mm / min, and the stress during peeling is measured, and the obtained stress is used as the adhesion strength. Then the adhesion strength is evaluated according to the following benchmarks. The smaller the adhesion strength, the better the functional layer suppresses the occurrence of adhesion, that is, the higher the anti-adhesion property of the functional layer.
[0215] A: Adhesion strength is less than 4N / m
[0216] B: Adhesion strength is 4 N / m or more and less than 6 N / m
[0217] C: Adhesion strength is 6 N / m or more and less than 8 N / m
[0218] D: Adhesion strength is 8 N / m or more and less than 10 N / m
[0219] E: Adhesion strength is 10N / m or more
[0220] <Heat resistance of functional layer>
[0221] The functional layer spacer produced in the examples and comparative examples was cut into a square with a width of 12 cm and a length of 12 cm. A square with a side of 10 cm was drawn inside the obtained square piece as a test piece. Then, the test piece was placed in a constant temperature bath at 150°C. After being placed for 1 hour, the area change of the square drawn inside [={(area of the square before placement - area of the square after placement) / area of the square before placement}×100%)] was calculated as the heat shrinkage rate and evaluated according to the following criteria. The smaller the heat shrinkage rate, the better the heat resistance of the functional layer spacer.
[0222] A: Thermal shrinkage is less than 3%
[0223] B: Thermal shrinkage is 3% or more and less than 5%
[0224] C: Thermal shrinkage is 5% or more and less than 10%
[0225] D: Thermal shrinkage is more than 10%
[0226] <Electrolyte injection properties>
[0227] The electrolyte is injected into the lithium ion secondary battery before the electrolyte is injected in the embodiments and comparative examples. Then, the internal pressure of the lithium ion secondary battery is reduced to -100kPa and maintained in this state for 1 minute. Then heat sealing is implemented. Then, the electrode (positive electrode) is disassembled after 10 minutes, and the impregnation state of the electrolyte in the electrode is visually confirmed. Then it is evaluated according to the following benchmarks. In the electrode, the more parts that are impregnated with the electrolyte, the higher the electrolyte injection property.
[0228] A: The electrolyte is impregnated on all surfaces of the electrode.
[0229] B: The area of the electrode that is not impregnated with electrolyte is less than 1 cm 2 (Except impregnation on all surfaces)
[0230] C: In the electrode, the part not impregnated with electrolyte remains 1cm 2 above
[0231] <Cycle characteristics of secondary batteries>
[0232] The lithium-ion secondary batteries prepared in the examples and comparative examples were left to stand at a temperature of 25°C for 5 hours. Next, they were charged at a temperature of 25°C using a constant current method of 0.2C until the battery cell voltage reached 3.65V, and then aged at a temperature of 60°C for 12 hours. Then, they were discharged at a temperature of 25°C using a constant current method of 0.2C until the battery cell voltage reached 3.00V. Then, CC-CV charging was performed using a constant current method of 0.2C (the upper limit battery cell voltage was 4.20V), and CC discharge was performed using a constant current method of 0.2C until 3.00V. This 0.2C charge and discharge was repeated 3 times.
[0233] Then, at a temperature of 25° C., 100 cycles of charge and discharge were performed at a cell voltage of 4.20-3.00 V and a charge and discharge rate of 1.0 C. At this time, the discharge capacity of the first cycle was defined as X1, and the discharge capacity of the 100th cycle was defined as X2.
[0234] Then, the capacity retention rate ΔC′=(X2 / X1)×100(%) was calculated using the discharge capacity X1 and the discharge capacity X2, and the evaluation was performed according to the following criteria: A larger value of the capacity retention rate ΔC′ indicates better cycle characteristics of the secondary battery.
[0235] A: Capacity retention rate ΔC′ is 93% or more
[0236] B: Capacity retention rate ΔC′ is 90% or more and less than 93%
[0237] C: Capacity retention rate ΔC′ is 87% or more and less than 90%
[0238] D: Capacity retention rate ΔC′ is less than 87%
[0239] <Output Characteristics of Secondary Battery>
[0240] The lithium-ion secondary batteries prepared in the embodiments and comparative examples are charged to 4.3V by constant current constant voltage (CCCV) at a temperature of 25°C to prepare battery cells. The prepared battery cells are discharged to 3.0V by constant current method of 0.2C and 1.5C to obtain the capacity. Then, the discharge capacity retention rate represented by the capacitance ratio [= (capacity at 1.5C / capacity at 0.2C) × 100 (%)] is obtained. This measurement is performed on 5 battery cells of the lithium-ion secondary battery. Then, the average value of the discharge capacity retention rate of each battery cell is obtained and evaluated according to the following criteria. The larger the average value of the discharge capacity retention rate, the better the output characteristics of the secondary battery.
[0241] A: The average discharge capacity retention rate is more than 90%
[0242] B: The average value of the discharge capacity retention rate is 85% or more and less than 90%
[0243] C: The average value of the discharge capacity retention rate is 75% or more and less than 85%
[0244] D: The average value of discharge capacity retention rate is less than 75%
[0245] <Powdering resistance of functional layer>
[0246] The functional layer spacer produced in the examples and comparative examples was cut into 5 cm × 5 cm pieces, and the mass (a) of the functional layer spacer sheet was measured. Next, the functional layer spacer sheet was placed in a 500 ml glass bottle and shaken at 300 rpm for 3 hours using an oscillator. Then, the mass (b) of the functional layer spacer sheet after shaking was measured, and the powder loss rate was calculated according to the following formula (II).
[0247] Powder loss rate (mass %) = [(ab) / a] × 100... (II)
[0248] Then, the powder falling resistance of the functional layer was evaluated according to the following criteria: The smaller the value of the powder falling rate, the less the components constituting the functional layer such as the particulate polymer fell off from the functional layer, and the better the powder falling resistance.
[0249] A: Powder loss rate is less than 1% by mass
[0250] B: Powder loss rate is 1 mass % or more and less than 3 mass %
[0251] C: Powder loss rate is 3% by mass or more and less than 5% by mass
[0252] D: Powder loss rate is 5% by mass or more
[0253] (Example 1)
[0254] <Preparation of granular polymer (A)>
[0255] [Preparation of Monomer Composition (A)]
[0256] 81.9 parts of styrene as an aromatic vinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed to prepare a monomer composition (A).
[0257] [Preparation of Metal Hydroxide]
[0258] An aqueous solution (A2) in which 5.6 parts of sodium hydroxide was dissolved in 50 parts of ion-exchanged water was slowly added to an aqueous solution (A1) in which 8 parts of magnesium chloride was dissolved in 200 parts of ion-exchanged water under stirring to prepare a colloidal dispersion (A) containing magnesium hydroxide as a metal hydroxide.
[0259] [Suspension polymerization method]
[0260] The granular polymer (A) is prepared by suspension polymerization. Specifically, the monomer composition (A) obtained as described above is added to the colloidal dispersion (A) containing magnesium hydroxide, and after further stirring, 2.0 parts of tert-butyl peroxy-2-ethylhexanoate (manufactured by NOF CORPORATION, "PERBUTYL (registered trademark) O") as a polymerization initiator are added to obtain a mixed solution. The obtained mixed solution is high-shear stirred for 1 minute at a rotation speed of 15000 rpm using a tandem emulsifier disperser (manufactured by Pacific Industrial Co., Ltd., "Cavitron") to form droplets of the monomer composition (A) in the colloidal dispersion (A) containing magnesium hydroxide.
[0261] The colloidal dispersion (A) containing magnesium hydroxide in which droplets of the monomer composition (A) were formed was added to a reactor, and the temperature was raised to 90° C. to carry out polymerization reaction for 5 hours to obtain an aqueous dispersion containing a particulate polymer (A).
[0262] The volume average particle size, particle size distribution and electrolyte swelling degree of the particulate polymer (A) were measured using the aqueous dispersion containing the particulate polymer (A).
[0263] Furthermore, while stirring the aqueous dispersion containing the granular polymer (A), sulfuric acid was added dropwise at room temperature (25°C) to perform acid washing until the pH was 6.5 or less. Next, filtration separation was performed, and 500 parts of ion exchange water was added to the obtained solid component to make it slurry again, and the water washing treatment (washing, filtration and dehydration) was repeated several times. Then, filtration separation was performed, and the obtained solid component was added to the container of a dryer and dried at 40°C for 48 hours to obtain a dried granular polymer (A).
[0264] The glass transition temperature and average circularity of the obtained particulate polymer (A) were measured.
[0265] <Preparation of Aqueous Dispersion Containing Binder (α)>
[0266] In a reactor equipped with a stirrer, 70 parts of ion exchange water, 0.15 parts of sodium lauryl sulfate (manufactured by Kao Corporation, "EMAL (registered trademark) 2F") as an emulsifier, and 0.5 parts of ammonium persulfate as a polymerization initiator were supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0267] On the other hand, in another container, 50 parts of ion exchange water, 0.5 parts of sodium dodecylbenzenesulfonate as a dispersion stabilizer, 94 parts of n-butyl acrylate as a (meth)acrylate monomer, 2 parts of methacrylic acid as an acid group-containing monomer and 2 parts of acrylonitrile as a nitrile group-containing monomer, and 1 part of allyl methacrylate and 1 part of allyl glycidyl ether as crosslinking monomers were mixed to prepare a monomer composition (α).
[0268] The obtained monomer composition (α) was continuously added to the reactor having a stirrer for 4 hours to carry out polymerization. During the addition, the reaction was carried out at 60°C. After the addition was completed, the mixture was further stirred at 70°C for 3 hours, and then the reaction was terminated to obtain an aqueous dispersion of a granular binder (α) as an acrylic polymer. The obtained granular binder (α) had a volume average particle size of 0.25 μm and a glass transition temperature of -40°C.
[0269] <Preparation of slurry composition>
[0270] 0.5 parts of polyacrylic acid as a dispersant were added to 100 parts of alumina as inorganic particles (manufactured by Sumitomo Chemical Co., Ltd., "AKP3000", volume average particle size: 0.7 μm), 6 parts of an aqueous dispersion containing a binder (α) and 1.5 parts of carboxymethyl cellulose as a thickener were added in terms of solid content, ion exchange water was added to make the solid content concentration 55%, and the mixture was mixed using a ball mill to obtain a pre-mixing slurry.
[0271] 0.2 parts of sodium dodecylbenzenesulfonate (Kao Corporation, "NEOPELEX G-15") as a surfactant was added to 100 parts of the granular polymer (A), mixed so that the solid content concentration was 40%, and the obtained mixed solution was added to the pre-mixed slurry obtained as described above. Ion exchange water was further added so that the solid content concentration was 40%, and a slurry composition (composition for functional layer) having a mixing ratio of inorganic particles (alumina) and granular polymer (A) as shown in Table 1 was obtained.
[0272] <Production of Spacer with Functional Layer>
[0273] A polyethylene microporous film (thickness: 12 μm) was prepared as a spacer substrate. The slurry composition obtained as described above was applied to one side of the spacer substrate by a rod coating method. Next, the spacer substrate coated with the slurry composition was dried at 50°C for 1 minute to form a functional layer. The same operation was performed on the other side of the spacer substrate to prepare a spacer with a functional layer having functional layers on both sides of the spacer substrate. In addition, the thickness of the inorganic particle layer in each functional layer was 2.0 μm.
[0274] <Production of positive electrode>
[0275] Mix 100 parts of LiCoO as the positive electrode active material 2 (volume average particle size: 12 μm), 2 parts of acetylene black (made by Denka Co., Ltd., "HS-100") as a conductive material, 2 parts of polyvinylidene fluoride (made by KUREHA CORPORATION, "#7208") as a binder for the positive electrode composite material layer in terms of solid content, and N-methylpyrrolidone as a solvent, so that the total solid content concentration is 70%. These are mixed by a planetary mixer to prepare a slurry composition for the positive electrode.
[0276] Using a notch wheel coater, the above-mentioned positive electrode slurry composition is applied to an aluminum foil with a thickness of 20 μm as a current collector in a manner such that the film thickness after drying is about 150 μm, and it is dried. The drying is carried out by transporting the aluminum foil in an oven at 60 ° C for 2 minutes at a speed of 0.5 m / min. Then, it is heat treated at 120 ° C for 2 minutes to obtain a positive electrode raw material before pressing. The positive electrode raw material before pressing is rolled using a roller press to obtain a pressed positive electrode having a positive electrode composite material layer (thickness: 60 μm).
[0277] <Production of negative electrode>
[0278] In a 5MPa pressure-resistant container with a stirrer, 33 parts of 1,3-butadiene, 3.5 parts of itaconic acid, 63.5 parts of styrene, 0.4 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion exchange water, and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the polymerization was initiated by heating to 50°C. When the polymerization conversion rate reached 96%, the reaction was terminated to obtain a mixture containing a binder (SBR) for a negative electrode composite material layer. A 5% aqueous sodium hydroxide solution was added to the mixture containing a binder for a negative electrode composite material layer, and after adjusting the pH to 8, unreacted monomers were removed by heating and reduced pressure distillation. Then, it was cooled to below 30°C to obtain the desired aqueous dispersion containing a binder for a negative electrode composite material layer.
[0279] 80 parts of artificial graphite (volume average particle size: 15.6 μm) as the negative electrode active material (1) and 16 parts of silicon-based active material SiOx (volume average particle size: 4.9 μm) as the negative electrode active material (2) were mixed with 2.5 parts of a 2% aqueous solution of carboxymethyl cellulose sodium salt (manufactured by NIPPON PAPER INDUSTRIES CO., Ltd., "MAC350HC") as a viscosity modifier and ion exchange water in terms of solid content, and the mixture was adjusted to a solid content concentration of 68%, and then further mixed at 25° C. for 60 minutes. The solid content concentration was further adjusted to 62% with ion exchange water, and then further mixed at 25° C. for 15 minutes to obtain a mixed solution. To the mixed solution, 1.5 parts of the aqueous dispersion containing the binder for the negative electrode composite material layer and ion exchange water in terms of solid content were added to adjust the final solid content concentration to 52%, and then further mixed for 10 minutes to obtain a mixed solution. The mixed solution was degassed under reduced pressure to obtain a negative electrode slurry composition having good fluidity.
[0280] Using a notch wheel coater, the above-mentioned negative electrode slurry composition is applied to a copper foil with a thickness of 20 μm as a current collector in a manner such that the film thickness after drying is about 150 μm, and it is dried. The drying is carried out by transporting the copper foil in an oven at 60°C for 2 minutes at a speed of 0.5 m / min. Then, it is heat treated at 120°C for 2 minutes to obtain the negative electrode raw material before pressing. The negative electrode raw material before pressing is rolled using a roller press to obtain a pressed negative electrode having a negative electrode composite material layer (thickness: 80 μm).
[0281] The separator with a functional layer, the positive electrode, and the negative electrode obtained as described above were used to evaluate process adhesion, anti-blocking property of the functional layer, heat resistance of the functional layer, and powdering resistance of the functional layer.
[0282] <Manufacturing of lithium-ion secondary batteries>
[0283] The pressed positive electrode produced as described above is cut into a rectangle of 49 cm × 5 cm and placed in a manner that the surface on the positive electrode composite material layer side is on the upper side. The above-mentioned functional layer separator cut into 120 cm × 5.5 cm is arranged on the positive electrode composite material layer so that the positive electrode is located on one side of the length direction of the functional layer separator. Furthermore, the pressed negative electrode produced as described above is cut into a rectangle of 50 cm × 5.2 cm and arranged on the functional layer separator so that the surface on the negative electrode composite material layer side faces the functional layer separator and the negative electrode is located on the other side of the length direction of the functional layer separator. Then, the obtained stack is wound by a winding machine to obtain a wound body. After the wound body is pressed at 70°C and 1 MPa to form a flat body, it is wrapped with an aluminum packaging material outer packaging as the outer packaging of the battery, and the electrolyte is injected in a manner that no air remains [Solvent: ethylene carbonate / diethyl carbonate / vinyl carbonate (volume ratio) = 68.5 / 30 / 1.5, electrolyte: LiPF with a concentration of 1M 6 ]. Then, the opening of the outer package of the aluminum packaging material was heat-sealed at a temperature of 150° C. to produce a wound lithium ion secondary battery with a capacity of 800 mAh.
[0284] The obtained lithium ion secondary battery was used to evaluate the electrolyte injection property, cycle characteristics, and output characteristics of the secondary battery.
[0285] (Example 2)
[0286] When preparing the slurry composition, the granular polymer (B) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0287] <Preparation of granular polymer (B)>
[0288] A granular polymer (B) was prepared in the same manner as in Example 1 except that the colloid dispersion (B) containing magnesium hydroxide was used instead of the colloid dispersion (A) containing magnesium hydroxide as the metal hydroxide.
[0289] The colloidal dispersion (B) containing magnesium hydroxide was prepared by slowly adding an aqueous solution (B2) of 7.0 parts of sodium hydroxide in 50 parts of ion-exchanged water to an aqueous solution (B1) of 10.0 parts of magnesium chloride in 200 parts of ion-exchanged water under stirring.
[0290] (Example 3)
[0291] When preparing the slurry composition, the granular polymer (C) prepared as described below is used instead of the granular polymer (A). In addition, the amount of sodium dodecylbenzene sulfonate used as an emulsifier is adjusted to 0.2 parts relative to a total of 100 parts of granular polymer and aluminum oxide. In addition, the same method as in Example 1 is used to prepare a functional layer spacer, a positive electrode and a negative electrode to obtain a lithium ion secondary battery. Then, various measurements and evaluations are performed in the same manner as in Example 1. The results are shown in Table 1.
[0292] <Preparation of granular polymer (C)>
[0293] A granular polymer (C) was obtained by the same operation as in Example 1 except that 0.3 parts of sodium dodecylbenzenesulfonate was used instead of the colloidal dispersion (A) containing magnesium hydroxide as the metal hydroxide when preparing the granular polymer.
[0294] (Example 4)
[0295] When preparing the slurry composition, the granular polymer (D) prepared as described below was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0296] <Preparation of granular polymer (D)>
[0297] A granular polymer (D) was prepared in the same manner as in Example 1 except that the colloid dispersion (D) containing magnesium hydroxide was used instead of the colloid dispersion (A) containing magnesium hydroxide as the metal hydroxide.
[0298] A colloidal dispersion (D) containing magnesium hydroxide was prepared by slowly adding an aqueous solution (D2) of 4.2 parts of sodium hydroxide in 50 parts of ion-exchanged water to an aqueous solution (D1) of 6.0 parts of magnesium chloride in 200 parts of ion-exchanged water under stirring.
[0299] (Example 5)
[0300] When preparing the slurry composition, the granular polymer (E) prepared as follows was used instead of the granular polymer (A) by using the emulsion polymerization coagulation method, and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0301] <Preparation of granular polymer (E)>
[0302] (1) Preparation of resin particles
[0303] 81.9 parts of styrene as an aromatic vinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed in a flask to prepare a monomer composition (E).
[0304] On the other hand, in a separable flask, 0.7 parts of sodium dodecylbenzenesulfonate as an anionic surfactant was dissolved in 373 parts of ion-exchanged water to prepare a surfactant solution.
[0305] The monomer composition (E) obtained as described above was added to the surfactant solution, and dispersed using an emulsifying disperser (manufactured by M Technique Co., Ltd., “CLEARMIX”) to prepare an emulsified dispersion of the monomer composition (E).
[0306] After adding 400 parts of ion exchange water to the obtained emulsified dispersion, an aqueous solution containing 2.1 parts of potassium persulfate as a polymerization initiator (an aqueous solution prepared by dissolving 2.1 parts of potassium persulfate in 39.6 parts of ion exchange water) and 1.9 parts of n-octyl mercaptan as a molecular weight regulator were added, and polymerization was carried out at 80° C. for 3 hours (first stage polymerization).
[0307] After adding 3.2 parts of an aqueous solution containing potassium persulfate as a polymerization initiator (an aqueous solution prepared by dissolving 3.2 parts of potassium persulfate in 61.3 parts of ion-exchanged water), 81.1 parts of styrene as an aromatic vinyl monomer, 12.0 parts of methacrylic acid and 36.8 parts of n-butyl acrylate as (meth)acrylate monomer units, and 2.1 parts of n-octyl mercaptan as a molecular weight modifier were added dropwise. After the dropwise addition, polymerization was carried out while maintaining the temperature (80° C.) for 2 hours (second stage polymerization).
[0308] After the polymerization, the reaction solution was cooled with water to obtain a dispersion solution containing resin fine particles.
[0309] (2) Preparation of resin particles
[0310] 150 parts of the dispersion containing resin particles obtained as described above and 645 parts of ion exchange water were added to a flask and stirred. The temperature of the obtained dispersion was adjusted to 30°C, and then sodium hydroxide aqueous solution (concentration: 5 mol / L) was added until the pH reached 10.
[0311] Next, an aqueous solution prepared by dissolving 32 parts of magnesium chloride hexahydrate in 32 parts of ion exchanged water was added to the above dispersion under stirring at 30° C. for 10 minutes. Then, while the dispersion was heated to 90° C. over 60 minutes and continued to be stirred and heated, aggregation due to salting out of the resin fine particles and fusion due to heating were performed to form resin particles.
[0312] Then, while continuing to stir and heat, the particle size of the resin particles was measured using a particle size measuring machine (manufactured by Beckman Coulter, "Multisizer"). When the volume average particle size of the formed resin particles reached 3 μm, an aqueous solution prepared by dissolving 8.8 parts of sodium chloride in 57.7 parts of ion exchange water was added to terminate the salting out and fusion. Heating and stirring were continued at 90° C. for 3 hours to control the particle shape, thereby obtaining a dispersion containing a particulate polymer (E).
[0313] The dispersion containing the particulate polymer (E) was dehydrated, washed with ion-exchanged water, and then dried in a vacuum dryer at a pressure of 30 torr and a temperature of 50° C. for one day to obtain a particulate polymer (E).
[0314] (Example 6)
[0315] When preparing the slurry composition, the granular polymer (F) prepared by the pulverization method was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0316] <Preparation of granular polymer (F)>
[0317] 81.9 parts of styrene as an aromatic vinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer were mixed in toluene. 0.5 parts of azobisisobutyronitrile (AIBN) as a polymerization initiator were added and reacted at 70°C for 10 hours. After the reaction, a precipitate was generated with methanol and vacuum dried to obtain a polymer (F). Next, the obtained polymer (F) was pulverized using a jet mill. The pulverized material was classified using an air flow splitter (manufactured by Hosokawa Micron Corporation, "100ATP").
[0318] The classified pulverized product was then subjected to a thermal spheroidization treatment to obtain a granular polymer (F). The thermal spheroidization treatment was performed at a temperature of 270° C. using a thermal spheroidization device (manufactured by Nippon Pneumatic Mfg. Co., Ltd., “SFS3 Model”).
[0319] (Example 7)
[0320] When preparing the slurry composition, the granular polymer (G) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 1.
[0321] <Preparation of granular polymer (G)>
[0322] A granular polymer (G) was prepared by carrying out the same operation as in Example 1 except that the monomer composition (G) was used instead of the monomer composition (A) when preparing the granular polymer.
[0323] The monomer composition (G) was prepared by mixing 20.9 parts of n-butyl acrylate as a (meth)acrylate monomer, 20 parts of acrylonitrile as a nitrile group-containing monomer, 59 parts of methyl methacrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer.
[0324] (Example 8)
[0325] When preparing the slurry composition, the granular polymer (H) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0326] <Preparation of granular polymer (H)>
[0327] A granular polymer (H) was prepared by the same operation as in Example 1 except that the monomer composition (H) was used instead of the monomer composition (A) when preparing the granular polymer and the obtained granular polymer was further subjected to fine powder and coarse powder cutting treatment.
[0328] Specifically, the monomer composition (H) was prepared by mixing 60 parts of styrene as an aromatic vinyl monomer, 39.9 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer.
[0329] Then, the granular polymer obtained using the monomer composition (H) was subjected to a fine powder and coarse powder cutting treatment using a classifier (manufactured by Hosokawa Micron Corporation, "Alpine") to obtain a granular polymer (H).
[0330] (Example 9)
[0331] When preparing the slurry composition, the granular polymer (I) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0332] <Preparation of granular polymer (I)>
[0333] In the suspension polymerization method, the same operation as in Example 1 was carried out except that the time for high shear stirring was changed to 10 seconds to obtain a particulate polymer (I).
[0334] (Example 10)
[0335] When preparing the slurry composition, the mixing ratio of alumina and particulate polymer (A) in the slurry composition was adjusted to a volume ratio [alumina: particulate polymer (A)] of 80:20. The same method as in Example 1 was used to prepare a functional layer separator, a positive electrode and a negative electrode to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0336] (Example 11)
[0337] When preparing the slurry composition, the mixing ratio of alumina and particulate polymer (A) in the slurry composition was adjusted to a volume ratio [alumina: particulate polymer (A)] of 55:45. The same method as in Example 1 was used to prepare a functional layer separator, a positive electrode and a negative electrode to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0338] (Example 12)
[0339] When preparing the slurry composition, the granular polymer (J) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0340] <Preparation of granular polymer (J)>
[0341] A granular polymer (J) was prepared by carrying out the same operation as in Example 1 except that the monomer composition (J) was used instead of the monomer composition (A) when preparing the granular polymer.
[0342] The monomer composition (J) was prepared by mixing 35 parts of styrene as an aromatic vinyl monomer, 64.9 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer.
[0343] (Example 13)
[0344] When preparing the slurry composition, the granular polymer (K) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.
[0345] <Preparation of granular polymer (K)>
[0346] A granular polymer (K) was prepared by carrying out the same operation as in Example 1 except that the monomer composition (K) was used instead of the monomer composition (A) when preparing the granular polymer.
[0347] The monomer composition (K) was prepared by mixing 89.9 parts of styrene as an aromatic vinyl monomer, 10 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer.
[0348] (Example 14)
[0349] When preparing the slurry composition, the aqueous dispersion containing the binding material (α) is replaced with the aqueous dispersion containing the binding material (β) prepared as follows, and otherwise, the functional layer separator, the positive electrode and the negative electrode are prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations are performed in the same manner as in Example 1. The results are shown in Table 2.
[0350] <Preparation of Aqueous Dispersion Containing Binder (β)>
[0351] In a reactor equipped with a stirrer, 70 parts of ion exchange water, 0.15 parts of polyoxyethylene lauryl ether (manufactured by Kao Corporation, "EMULGEN (registered trademark) 120") as an emulsifier, and 0.5 parts of ammonium persulfate as a polymerization initiator were supplied, the gas phase was replaced with nitrogen, and the temperature was raised to 60°C.
[0352] On the other hand, in another container, 50 parts of ion-exchanged water, 0.5 parts of polyoxyethylene lauryl ether (manufactured by Kao Corporation, "EMULGEN (registered trademark) 120") as an emulsifier, 70 parts of 2-ethylhexyl acrylate as an alkyl (meth)acrylate monomer, 25 parts of styrene as an aromatic vinyl monomer, 1.7 parts of allyl glycidyl ether and 0.3 parts of allyl methacrylate as crosslinking monomers, and 3 parts of acrylic acid as an acid group-containing monomer were mixed to prepare a monomer composition (β).
[0353] The obtained monomer composition (β) was continuously added to the above-mentioned reactor with a stirrer over 4 hours to perform polymerization. During the addition process, the reaction was carried out at 70°C. After the addition was completed, the mixture was further stirred at 80°C for 3 hours, and then the reaction was terminated to obtain an aqueous dispersion containing a granular binder (β). The obtained granular binder (β) had a volume average particle size of 0.3 μm and a glass transition temperature of -35°C.
[0354] (Example 15)
[0355] When preparing the slurry composition, the aqueous dispersion containing the binding material (α) is replaced with the aqueous dispersion containing the binding material (γ) prepared as follows, and otherwise, the functional layer separator, the positive electrode and the negative electrode are prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations are performed in the same manner as in Example 1. The results are shown in Table 2.
[0356] <Preparation of Aqueous Dispersion Containing Binder (γ)>
[0357] A mixture containing 33 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 62 parts of styrene as an aromatic vinyl monomer, 4 parts of itaconic acid as a carboxylic acid group-containing monomer, 0.3 parts of tert-dodecyl mercaptan as a chain transfer agent, and 0.3 parts of sodium lauryl sulfate as an emulsifier was placed in container A. Then, the mixture in container A was added to pressure container B, and 1 part of potassium persulfate as a polymerization initiator was added to pressure container B to initiate polymerization. At this time, the reaction temperature was maintained at 75°C.
[0358] Furthermore, 4 hours after the initiation of polymerization (i.e., after 70% of the mixture was added to the pressure vessel B), 1 part of 2-hydroxyethyl acrylate (2-hydroxyethyl acrylate) as a hydroxyl group-containing monomer was added to the pressure vessel B over 1 hour and 30 minutes.
[0359] After 5 hours and 30 minutes from the initiation of polymerization, the addition of the total amount of the above-mentioned monomers was completed, and then the temperature was further raised to 85° C. to allow the reaction to proceed for 6 hours.
[0360] When the polymerization conversion rate reaches 97%, the reaction is cooled and terminated to obtain a mixture containing a granular polymer (γ1). A 5% sodium hydroxide aqueous solution is added to the obtained mixture to adjust the pH to 8. Then, the unreacted monomers are removed by heating and distilling under reduced pressure. Then, cooling is performed to obtain an aqueous dispersion (solid content concentration: 40%) containing a styrene-butadiene copolymer (SBR) as a granular binder (γ). The volume average particle size of the obtained granular binder (γ) is 0.18μm and the glass transition temperature is 15°C.
[0361] (Comparative Example 1)
[0362] When preparing the slurry composition, the seed polymerization method was used instead of the granular polymer (A) and the granular polymer (V) prepared as follows was used. Otherwise, the same method as in Example 1 was used to prepare a functional layer separator, a positive electrode and a negative electrode to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0363] <Preparation of granular polymer (V)>
[0364] In a 5 MPa pressure-resistant container equipped with a stirrer, a monomer composition (V1) containing 79.9 parts of styrene as an aromatic vinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 2 parts of methacrylic acid as an acid group-containing monomer unit and 0.1 parts of ethylene glycol dimethacrylate as a di(meth)acrylate monomer was added, and 1 part of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion exchange water and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 60° C. to initiate polymerization.
[0365] When the polymerization conversion rate reached 96%, the reaction was terminated by cooling the mixture to obtain seed particles (V S 1) aqueous dispersion. In addition, the seed particles (V S 1) has a volume average particle size of 500 nm.
[0366] Further, the seed particles (V S A monomer composition (V2) comprising 2077.4 parts of styrene as an aromatic vinyl monomer, 494 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 52 parts of methacrylic acid as an acid group-containing monomer and 2.6 parts of ethylene glycol dimethacrylate as a di(meth)acrylate monomer was added to the aqueous dispersion of 1), and after sufficient stirring, the temperature was raised to 60° C. to initiate polymerization.
[0367] When the polymerization conversion rate reached 96%, the reaction was terminated by cooling the mixture to obtain seed particles (V S 2) aqueous dispersion. In addition, the seed particles (V S 2) The volume average particle size is 1.5 μm.
[0368] Furthermore, the seed particles (V S 559.3 parts of styrene as an aromatic vinyl monomer, 133 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 14 parts of methacrylic acid as an acid group-containing monomer and 0.7 parts of ethylene glycol dimethacrylate as a di(meth)acrylate monomer were added to the aqueous dispersion of 2), and after sufficient stirring, the temperature was raised to 60° C. to initiate polymerization.
[0369] When the polymerization conversion rate reached 96%, the reaction was terminated by cooling, thereby obtaining an aqueous dispersion containing a particulate polymer (V).
[0370] (Comparative Example 2)
[0371] When preparing the slurry composition, the granular polymer (A) was replaced by the seed polymerization method and the granular polymer (W) prepared as follows was used. Otherwise, the same method as in Example 1 was used to prepare a functional layer separator, a positive electrode and a negative electrode to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0372] <Preparation of granular polymer (W)>
[0373] In a 5 MPa pressure-resistant container with a stirrer, a monomer composition (W1) containing 75 parts of styrene as an aromatic vinyl monomer, 20 parts of n-butyl acrylate as a (meth)acrylate alkyl ester monomer, 4 parts of methacrylic acid as an acid group-containing monomer and 1 part of ethylene glycol dimethacrylate as a di(meth)acrylate monomer was added, and 1.2 parts of sodium dodecylbenzene sulfonate as an emulsifier, 150 parts of ion exchange water and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 60°C to initiate polymerization.
[0374] When the polymerization conversion rate reached 96%, the reaction was terminated by cooling the mixture to obtain seed particles (W S 1) Aqueous dispersion.
[0375] Further, the seed particles (W S 1) was added with a monomer composition (W2) comprising 75,000 parts of styrene as an aromatic vinyl monomer, 20,000 parts of n-butyl acrylate as a (meth)acrylate monomer, 4,000 parts of methacrylic acid as an acid group-containing monomer and 1,000 parts of ethylene glycol dimethacrylate as a di(meth)acrylate monomer, and the mixture was stirred thoroughly and then heated to 60° C. to initiate polymerization.
[0376] When the polymerization conversion rate reached 96%, the reaction was terminated by cooling, thereby obtaining an aqueous dispersion containing a particulate polymer (W).
[0377] (Comparative Example 3)
[0378] When preparing the slurry composition, the granular polymer (X) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0379] <Preparation of granular polymer (X)>
[0380] The pelletized polymer (E) prepared in Example 5 was coarsely pulverized. The coarsely pulverized product was finely pulverized using a jet mill (manufactured by Hosokawa Micron Corporation, "200AFG") at a pulverizing air pressure of 500 (kPa) and a rotor rotation speed of 7000 (rpm) to obtain a pelletized polymer (X).
[0381] (Comparative Example 4)
[0382] When preparing the slurry composition, the granular polymer (Y) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0383] <Preparation of granular polymer (Y)>
[0384] When preparing the granular polymer, the same operation as in Example 1 was carried out except that the colloid dispersion liquid (Y) containing magnesium hydroxide prepared as follows was used instead of the colloid dispersion liquid (A) containing magnesium hydroxide used in Example 1, thereby obtaining a granular polymer (Y).
[0385] [Preparation of colloidal dispersion liquid (Y) containing magnesium hydroxide]
[0386] An aqueous solution (Y2) in which 2.8 parts of sodium hydroxide was dissolved in 50 parts of ion-exchanged water was slowly added to an aqueous solution (Y1) in which 4.0 parts of magnesium chloride was dissolved in 200 parts of ion-exchanged water under stirring to prepare a colloidal dispersion (Y) containing magnesium hydroxide.
[0387] (Comparative Example 5)
[0388] When preparing the slurry composition, the granular polymer (Z) prepared as follows was used instead of the granular polymer (A), and the functional layer separator, the positive electrode and the negative electrode were prepared in the same manner as in Example 1 to obtain a lithium ion secondary battery. Then, various measurements and evaluations were performed in the same manner as in Example 1. The results are shown in Table 3.
[0389] <Preparation of granular polymer (Z)>
[0390] In a 5 MPa pressure-resistant container equipped with a stirrer, a monomer composition (Z1) containing 79.9 parts of styrene as an aromatic vinyl monomer, 18 parts of 2-ethylhexyl acrylate as a (meth)acrylate monomer, 2 parts of methacrylic acid as an acid group-containing monomer, and 0.1 parts of ethylene glycol dimethacrylate as a crosslinking monomer was added, and 1 part of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion exchange water, and 0.5 parts of potassium persulfate as a polymerization initiator were added, and after sufficient stirring, the temperature was raised to 60° C. to initiate polymerization.
[0391] When the polymerization conversion rate reached 96%, the reaction was terminated by cooling, thereby obtaining an aqueous dispersion containing a particulate polymer (Z).
[0392] [Table 1]
[0393]
[0394] [Table 2]
[0395]
[0396] [Table 3]
[0397]
[0398] In addition, in Tables 1 to 3,
[0399] "ST" stands for styrene,
[0400] "2EHA" means 2-ethylhexyl acrylate,
[0401] "EDMA" means ethylene glycol dimethacrylate,
[0402] "BA" means n-butyl acrylate,
[0403] "AN" stands for acrylonitrile,
[0404] "MAA" means methacrylic acid,
[0405] "MMA" means methyl methacrylate,
[0406] "AGE" means allyl glycidyl ether,
[0407] "AMA" stands for allyl methacrylate,
[0408] "AA" means acrylic acid,
[0409] "SBR" means styrene-butadiene copolymer.
[0410] According to Tables 1 to 3, Examples 1 to 15 using a slurry composition (functional layer composition) comprising a granular polymer having an average roundness of 0.90 or more and less than 0.99 and a volume average particle size of 1.0 μm or more and 10.0 μm or less, a binder, and inorganic particles can form a functional layer that can suppress powder loss and ensure high heat resistance while allowing the separator and the electrode to be firmly bonded in the electrolyte. It is also known that by using this functional layer, a secondary battery with good electrochemical characteristics can be obtained.
[0411] Industrial Applicability
[0412] According to the present invention, there can be provided a composition for an electrochemical element functional layer which can effectively form an electrochemical element functional layer that can suppress powdering and can exhibit excellent adhesiveness while ensuring sufficient heat resistance.
[0413] Furthermore, according to the present invention, it is possible to provide a functional layer for an electrochemical element that can suppress powdering and exhibit excellent adhesiveness while ensuring sufficient heat resistance.
[0414] Furthermore, according to the present invention, it is possible to provide an electrochemical device that can exhibit excellent electrochemical characteristics.
Claims
1. A composition for an electrochemical element functional layer, comprising a granular polymer, a binding material and inorganic particles, The average circularity of the particulate polymer is 0.90 or more and less than 0.99, and The volume average particle size of the particulate polymer is 3.2 μm or more and 8.0 μm or less, The electrolyte swelling degree of the granular polymer is 1.0 times or more and 10 times or less, In the functional layer formed using the electrochemical element functional layer composition, the ratio of the volume average particle size of the granular polymer to the thickness of the layer formed by overlapping the inorganic particles along the thickness direction of the functional layer, i.e., the volume average particle size of the granular polymer / the thickness of the layer formed by overlapping the inorganic particles along the thickness direction of the functional layer is 0.75 or more and 5.0 or less, The glass transition temperature of the particulate polymer is 10° C. or higher and 90° C. or lower. The bonding material is a conjugated diene polymer or an acrylic polymer. The average roundness is the average value of the roundness, and the roundness is represented by the following formula (I): Circularity = circumference of a circle equal to the projected area of the particulate polymer / circumference of the projected image of the particulate polymer (I).
2. The composition for an electrochemical element functional layer according to claim 1, wherein The particle size distribution of the particulate polymer is 1.10 or more and 1.50 or less.
3. The composition for an electrochemical element functional layer according to claim 1 or 2, wherein The mixing ratio of the inorganic particles to the particulate polymer is 95:5 to 55:45 in volume ratio.
4. The composition for an electrochemical element functional layer according to claim 1 or 2, wherein The particulate polymer comprises aromatic vinyl monomer units. 5 . An electrochemical device functional layer formed using the electrochemical device functional layer composition according to claim 1 . 6 . An electrochemical device comprising the functional layer for an electrochemical device according to claim 5 .
Citation Information
Patent Citations
Electrode for secondary battery, binder for secondary battery electrode, manufacturing method and secondary battery
JP2012204303A
Separator for secondary cell
WO2013151144A1
Slurry composition for secondary battery porous membrane
JP2013206846A
Wound electrode element for nonaqueous electrolyte secondary batteries, nonaqueous electrolyte secondary battery using the same, and method for manufacturing wound electrode element for nonaqueous electrolyte secondary batteries
JP2015115266A
Composition for nonaqueous secondary battery adhesion layer, adhesion layer for nonaqueous secondary battery, nonaqueous secondary battery member, nonaqueous secondary battery, and method for manufacturing adhesion layer for nonaqueous secondary battery
JP2016100149A